SCJD Exam with J2SE 5 - Monkhouse, Andrew; Camerlengo, Terry (Apress : Imprint: Apress, 2006)
You already know how crucial certification is within the Java community. SCJD Exam with J2SE 5, Second Edition is a valuable guide to prepare for the exam. This book has been updated for the Java version J2SE 5.0, and works its way through a project with requirements and structure similar to the project you'll encounter in the exam. Upon reading this book, you'll become intimately familiar with key concepts, challenges, and pitfalls that the exam is likely to test you on.